ENTREPRENEUR MATHEMATICS (ENTREMATH): TEACHING MATERIALS IN IMPROVING PROBLEM SOLVING SKILLS - Yopi Romafilani; Neneng Aminah; Romarzila Omar (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Mathematics in SMK is a general subject that must be understood, in fact many students avoid mathematics, one of the reasons is because the teaching materials have not facilitated the characteristics of students. The purpose of this study is to evaluate the validity, application, and effectiveness of digital entrepreneurship-based mathematics modules in improving students' problem-solving abilities. With students from class XI vocational courses, this research applies the ADDIE paradigm. Data were obtained using Entremath validation questionnaires, student and teacher response questionnaires, and post-test scores. The results show that mathematics is entrepreneur-based. Entremath is considered to fall under the very valid criteria. It is declared practical, with 86.9% of students and 96% of teachers belonging to the very practical category, and effectively denoted by a sig value greater than table t. The results of entrepreneurial mathematics research contain qualities that can be used for mathematics educationMatematika di SMK merupakan mata pelajaran umum yang harus dipahami, nyatanya banyak siswa yang menghindari matematika, salah satu penyebabnya adalah karena bahan ajar yang belum memfasilitasi karakteristik siswa. Tujuan penelitian ini adalah untuk mengevaluasi validitas, penerapan, dan efektivitas modul digital matematika berbasis kewirausahaan dalam meningkatkan kemampuan pemecahan masalah siswa. Dengan peserta didik kelas XI program studi SMK, penelitian ini menerapkan paradigma ADDIE. Data diperoleh dengan menggunakan angket validasi Entremath, angket respon siswa dan guru, serta nilai post-test. Hasilnya menunjukkan bahwa modul digital matematika berbasis wirausaha dianggap masuk dalam kriteria yang sangat valid. Dinyatakan praktis, dengan respon positif 86,9% dari siswa dan 96% dari guru termasuk dalam kategori sangat praktis, dan efektif ditunjukkan dengan nilai sig lebih besar dari t tabel. Hasil penelitian matematika kewirausahaan mengandung kualitas yang dapat digunakan untuk pendidikan matematika.